Le nuove generazioni e il Sessantotto. Tra mito e contro-mito - Raffini, Luca (SocietàMutamentoPolitica, 2018)
Sixty-eight is a complex, multi-faceted, ambiguous movement which nevertheless had a strong generational dimension. Starting from this assumption, the article reconstructs the characteristics of the movement and explores its protagonists and its different souls. We critically investigate the consequences of the movement on the cultural, social, political and economic level. The goal is to analyze the relations between the values of the Sixty-eight and the new generations. In order to do this, we investigate the specific features of the Italian Sixty-eight and how it changed the Italian society. More generally, we propose a critical reflection on the link between the diffusion of the values of the Sixty-eight and economic, social and political change. In particular, we explore two critical reading. The first one is Inglehart’s theory of the spread - and perhaps decline - of postmaterialist values and the transformations of politics. The second one is Boltanski and Chiapello’s theory about the raise of the “new spirit of capitalism”, in strict connection with the anti-authoritarian value orientation expressed by the Sixty-eight. In conclusion, we try to outline “affinities and divergences” between the political and social context of Sixty-eight and the contemporary context and to understand how today the new generations, in the context of profound change, contribute to the reinvention of politics.